Customer-Driven Evaluation of Service Quality in Nepal’s Banking Sector - Poudel, Aakriti; Niraula, Arjun (International Journal of Atharva, 2024)
Service quality is a critical determinant of customer satisfaction in the banking sector, where customers' perceptions of various service attributes directly influence their loyalty and engagement. In Nepal, understanding these perceptions is essential for banks to maintain competitiveness and improve service standards. This study utilized a quantitative approach to assess customer satisfaction across key service attributes in Nepal's banking sector. A structured questionnaire was distributed to 120 respondents, measuring their agreement with statements related to service quality using a Likert scale. Descriptive statistics, including frequency, percentage, and cumulative percent, were employed to analyze customer feedback. The results indicate that while customers largely appreciate the banks' modern facilities, neat-appearing employees, and secure services, there is a notable neutrality regarding the reliability of timely service delivery and problem-solving efforts. Furthermore, many respondents were neutral about the personal attention and enthusiasm provided by bank employees. However, a significant majority of customers expressed satisfaction with the banks’ ability to meet their needs, recommending the bank to others and intending to continue using its services. The analysis reveals that Nepalese banks perform well in terms of infrastructure and employee professionalism but have room for improvement in service reliability and responsiveness. Addressing these gaps can enhance customer satisfaction and loyalty, offering banks valuable direction for maintaining high service standards and improving customer engagement.